Multi-platform nano-immunosensor for aflatoxin M1 in milk. (14th April 2015) - Pal, Souvik; Sharma, Manoj Kumar; Chatterjee, Ratnamala; Bhand, Sunil
Abstract: A multi-platform detection based on hafnia nanoparticles (HfO2 NPs) has been developed for immunosensing of aflatoxin M1 (AFM1) as a model analyte. The fine-grained nanocrystal ceramic powder samples of HfO2 NPs were prepared using a solution based chemical method by easily available laboratory reagents. Highly specific monoclonal antibody was immobilized on HfO2 surface using novel chemical modification and crosslinking chemistry. The nano-immunosensor was investigated using the chemiluminescent sandwich enzyme-linked immunosorbent assay in the range 200–0.5 pg mL −1 . Simultaneously, the particles were also investigated photometrically. The developed immuno-sensor exhibited good linearity with a limit of detection 6.25 pg mL −1, sensitivity, selectivity and stability. The IC50 value was obtained at 61.48 pg mL −1 . Moreover, recovery of milk samples was close to 100%. Using the developed immuno-sensor, AFM1 was measurable even after 30 days at storage condition of 4 °C and as well as room temperature (at 28 °C). The miniaturised nano-immunosensor was used for high-throughput analysis (384 individual samples/40 min) of AFM1. To the best of our knowledge, this is the first report in which HfO2 NPs are used for the fabrication of a multi-platform immuno-sensor system for AFM1 in milk.